AMERICAN DREAM AS REFLECTED IN DAVID MAMET’S GLENGARRY GLEN ROSS - Mianani, Sindhy Sintya (International Journal of Humanity Studies (IJHS), 2019)
David Mamet is one of the greatest modern American playwrights whose works have dominated the stages during the twentieth century. His work entitled Glengarry Glen Ross is a great echo of the world about the businessmen in the United States. This study is devoted to the analysis of David Mamet’s Glengarry Glen Ross based on Marxism point of view, in which it focuses on the power praxis portrayed within its story.  By so, this study scrutinizes how American Dream creates unethical and immoral American corrupted society in Mamet's Glengarry Glen Ross and how the notion of American Dream is being challenged. The findings of this study show that the salesmen’s choices, preferences, wants and desires are affected by ideological practices. These ideological practices represent the production of corrupted ideology for the notion of American Dream is being reduced and merely an utopian notion. Thus, eventually, David Mamet’s Glengarry Glen Ross displays a deeper conception that the salesmen or working class people in general, are the subjects of the capitalism.DOI: 10.24071/ijhs.2019.030109